Return of socially-responsible stock index amid the pandemic - Isnaini Nuzula Agustin; Nathalia Kristiani (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2023)
This research aims to investigate the impact of the COVID-19 pandemic on socially responsible investment, specifically the SRI-KEHATI stock index on the Jakarta Stock Exchange. The study utilizes secondary data comprising 11,175 observations from 35 public companies, spanning from March 2, 2020, to December 31, 2021. Panel data regression is employed to examine the relationship between stock returns and confirmed COVID-19 cases, serving as the independent variable. The model is controlled for market capitalization, market-to-book ratio, and firm size. Additionally, Indonesia's lockdown policy is incorporated as a dummy variable. The findings reveal a significant negative impact of confirmed cases on SRI-KEHATI stock returns.